Synonymy in Idiomatic Expressions - Broz, Vlatko (Array, 2011)
This paper examines the paradigmatic semantic relationship of synonymy in several sets of different idiomatic expressions with similar meaning. It starts from the hypothesis that no synonyms have exactly the same meaning in all contexts or on all socio-cultural levels of language, and that corrective mechanisms operate to prevent absolute synonymy (such as one of the lexical units falling into disuse or acquiring different connotations in terms of stylistic markedness or register). One of the ways to test this hypothesis is to conduct a survey of native speakers, asking them whether selected idiomatic expressions are synonymous or not, as well as in which contexts and uses their meanings differ. The paper presents the results of this survey, in which 25 native speakers of English participated.